The evolving role of Asia in global finance - Cheung, Yin-Wong; Kakkar, Vikas; Ma, Guonan (Frontiers of economics and globalization ;, 2011)
The process of Asias rise to a position of eminence in global finance has accelerated in the wake of the international financial crisis, posing new opportunities and challenges to both the Asian economies and the global financial and trade systems. This volume represents a significant new endeavour to explore and understand the dynamics created by this process of transition. Specifically, it addresses the following four contemporary themes of the evolving role of Asia in global finance: (a) real and financial interactions among economies and across markets, both within Asia and beyond; (b) regional monetary cooperation in Asia; (c) the decoupling debate over Asias evolving economic and financial ties with major industrial economies; and (d) the changing roles of domestic finance and capital flows in the developing Asian economies. It sheds light on various dimensions of Asias economy and finance, ranging from business cycles, exchange rate movements, regional policy coordination, domestic financial development, capital flows, and financial market behaviour. These analyses are pooled in a book that is a must read for market participants, policymakers and academics alike.